Soil mycobiome in sustainable agriculture - Frąc, Magdalena; Hannula, Emilia Silja; Bełka, Marta; Salles, Joana Falcao; Jedryczka, Malgorzata (Frontiers in Microbiology, 2022)
The soil microbiome contributes to several ecosystem processes. It plays a key role in sustainable agriculture, horticulture and forestry. In contrast to the vast number of studies focusing on soil bacteria, the amount of research concerning soil fungal communities is limited. This is despite the fact that fungi play a crucial role in the cycling of matter and energy on Earth. Fungi constitute a significant part of the pathobiome of plants. Moreover, many of them are indispensable to plant health. This group includes mycorrhizal fungi, superparasites of pathogens, and generalists; they stabilize the soil mycobiome and play a key role in biogeochemical cycles. Several fungal species also contribute to soil bioremediation through their uptake of high amounts of contaminants from the environment. Moreover, fungal mycelia stretch below the ground like blood vessels in the human body, transferring water and nutrients to and from various plants. Recent advances in high-throughput sequencing combined with bioinformatic tools have facilitated detailed studies of the soil mycobiome. This review discusses the beneficial effects of soil mycobiomes and their interactions with other microbes and hosts in both healthy and unhealthy ecosystems. It may be argued that studying the soil mycobiome in such a fashion is an essential step in promoting sustainable and regenerative agriculture.